Beyond aesthetics : philosophical essays - Carroll, Noël, 1947- (Cambridge University Press, 2001)
"Beyond Aesthetics brings together philosophical essays addressing art and related issues by one of the foremost philosophers of art at work today. Countering conventional aesthetic theories - those maintaining that authorial intention, art history, morality, and emotional responses are irrelevant to the experience of art - Noel Carroll argues for a more pluralistic and commonsensical view in which all of these factors can play a legitimate role in our encounter with artworks. Throughout, the book combines philosophical theorizing with illustrative examples including works of high culture and the avant-garde, as well as works of popular culture, jokes, horror novels, and suspense films."--Jacket